Perlakuan Balita Dengan Manajemen Terpadu Balita Sakit (MTBS) Di Puskesmas Sukadana - Eko Saputro; Ersa Tri Fitriasari (CV. ULIL ALBAB CORP, 2022)
To provide standard services in Public Health Center takes a commitment from the Head of the Public Health Center and the commitment of the doctors as a motivator for nurses and midwives in addition to being a supervisor and receiving referrals. The continuity of the implementation of IMCI services is to maintain and to improve the quality of IMCI services by remaining consistent in improving the health facilities of the Public Health Center so that people who are far from the Public Helath Center can get the standard IMCI services and continue to innovate in developing utilization by developing human resources that are not only providing services to patients but also being able to realize the vision and mission of Public Health Center. The result of Poly IMCI research has been carried out have several points: 1) the customer comfort factor in receiving services by making several changes to the physical appearance of the room, 2) the completeness factor for supporting physical examination equipment (measuring height and body length, weighing infants and toddlers, measuring upper arm circumference), and 3) implementing innovation in the process of recording and classifying diseases using the IMCI application.